A Plant-Produced Bacteriophage Tailspike Protein for the Control of Salmonella - Miletic, Sean; Simpson, David J.; Szymanski, Christine M.; Deyholos, Michael K.; Menassa, Rima (Frontiers in Plant Science, 2016)
The receptor binding domain of the tailspike protein Gp9 from the P22 bacteriophage was recently shown to reduce colonization in the chicken gut. In this study, we transiently expressed the receptor binding domain of the Gp9 tailspike protein in Nicotiana benthamiana, and targeted it to the endoplasmic reticulum (ER) or to the chloroplast. Gp9 was also fused to either an elastin-like polypeptide (ELP) or hydrophobin I (HFBI) tag, which were previously described to improve accumulation levels of recombinant proteins. The highest levels of recombinant protein accumulation occurred when unfused Gp9 was targeted to the ER. Lower levels of chloroplast-targeted Gp9 were also detected. ELP-fused Gp9 was purified and demonstrated to bind to Salmonella enterica serovar Typhimurium in vitro. Upon oral administration of lyophilized leaves expressing Gp9-ELP to newly hatched chicks, we found that this tailspike protein has the potential to be used as a prophylactic to control Salmonella contamination in chickens.